LEARNING TO TEACH THROUGH REFLECTIVE PRACTICE - Tay Pei Lin; Jasmine Jain (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The paper explores how student teachers learn to be reflective classroom practitioners by understanding the meaning they attach to the term ‘reflective practice’, and subsequently how they put that meaning into practice in a teacher education programme. The two dimensions of reflective practice being investigated are: student teachers’ interpretation of reflective practice, and their individual experience of being a reflective practitioner based on this unique understanding. In teaching, the reflective practitioner model encourages student teachers to integrate themselves in the real world of practice by being aware of and reflecting on their own values, beliefs, thoughts and actions in making classroom decisions, and in engaging and dealing with the complexities that the real world of classroom poses rather than applying the educational knowledge and theories they learned unquestionably. Although there are well-established literature that supports the rationale for the reflective practitioner model in teacher education, there are also debates about the lack of understanding of this notion which affects how student teachers engage in reflective practice. Interview data suggest that student teachers’ perceived importance of reflective practice is influenced by the varied opportunities provided to them. Their experience in making situational judgements and depth of reflection are manifested as a result of critical interaction with various stakeholders. The understanding of reflective practice is important for educators and curriculum designers in general to develop effective reflective practitioners in a teacher education programme.